HUBUNGAN ANTARA KEYAKINAN DIRI DAN PERILAKU DISIPLIN BELAJAR DENGAN KEMANDIRIAN BELAJAR SISWA KELAS XI SMK SE-KABUPATEN BOJA - Harris Yuliawan; Eko Nusantoro (Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry, 2020)
This study aims to identify the relationship between Self Confidence and Discipline Learning Behavior with Learning Independence. This study uses a correlational design. Data were collected using self-confidence scale, learning discipline behavior questionnaire and learning independence scale of 289 students selected by cluster random sampling area technique. Hierarchical regression analysis results showed a positive prediction between self-confidence and learning discipline behavior with learning independence had a significant positive relationship (Î² = 0.622, Fcount = 181.313, t = 13.465, p = 0.00). This proves that the first hypothesis which reads